Dukungan Keluarga, Adaptasi Sosial terhadap Tingkat Anxietas Perawat Selama Pandemi COVID-19 di Puskesmas - Zadam Marita; Sigit Mulyono; Uswatun Khasanah; Mariam Dasat; Fauziah H Tambuala (Journal of Telenursing (JOTING), 2022)
This study examined how family support and social adaptation correlate to nurses' anxiety levels during the COVID-19 pandemic. This descriptive correlational study was conducted using Cross Sectional approach. Non Probability Sampling and Purposive Sampling techniques were employed to select 126 respondents who were assigned to answer validated questionnaires namely TMAS (Anxiety (Taylor Minnesota Anxiety Scale), PAIS-SR social adaptation (Psychosocial Adjustment to Illness), family support scale and work stress scale. Results the final analysis showed the level of family support, social adaptation and work stress experience correlate to nurses' anxiety levels during the COVID-19 pandemic. conclusion, the factors related to nurses anxiety during the COVID-19 pandemic are family support, social adaptation and the experience of nurses' work stres. Keywords: Anxiety, COVID-19, Social Adaptation, Family Support, Nurse